Integrated traditional Chinese and western medicine nursing of a patient with Guillain-Barre syndrome complicated with dissociative disorder (1例吉兰-巴雷综合征合并分离性障碍患者的中西医结合护理体会) - ZHOU Yuan (周媛); LI Qian (李倩); LIU Jianmei (刘健玫); CAI Chang (蔡畅); MA Haili (马海利); FENG Qingqing (冯青青) (Association of Integrative Nursing, 2024)
This article summarizes the treatment and integrated traditional Chinese and western medicine nursing experience of a patient with Guillain-Barre syndrome complicated with dissociative disorder. Through syndrome differentiation and nursing, Traditional Chinese Medicine characteristic nursing methods such as bamboo cupping therapy, moxibustion and five-tone music therapy were given according to the syndrome types and clinical symptoms, combined with psychotherapy and routine nursing interventions. The combined treatment of Traditional Chinese Medicine nursing techniques are effective to improve the muscle strength and relieve the uncomfortable symptoms of patients with Guillain-Barre syndrome complicated with dissociative disorder. (本文总结1例吉兰-巴雷综合征合并分离性障碍患者的中西医结合护理经验。基于护理评估和中医辨证, 在病情观察、生活指导、饮食护理等常规护理基础上, 采取竹罐、艾灸、五音疗法等中医护理适宜技术, 有效提高患者四肢肌力, 改善了患者不适症状。)